Infection-Induced Kidney Diseases - Prasad, Narayan; Patel, Manas Ranjan (Frontiers in Medicine, 2018)
Infections induced kidney diseases are concerns for clinicians because timely detection and treatment of infections may cure or, limit the extent of injury inflicted because of microorganisms causing infections. Infection inflicts kidney injuries by either direct invasion, or indirectly inducing immune mediated injuries, which manifest in forms post-infectious glomerulonephritis, or infection related glomerulonephritis etc. Clinical manifestations may be acute or chronic depending on the microorganisms, endemic/epidemic nature and source of infection. All microbials virus, bacteria, mycobacteria, fungus, and protozoa have been implicated in kidney diseases either causing direct kidney injuries or immune-mediated injuries. Infection control practices in large parts of world is limited by poverty, social behavior, high population density, deforestation, inadequate access to safe drinking water and poor health care facilities. Although, antimicrobials and vaccinations have successfully eradicated and cured many infectious diseases; however injudicious antimicrobial use and emergence of resistant organisms complicated the disease severity like secondary renal amyloidosis with chronic persistent infection. Re-emergence of various infections has been a recent pattern in developed world leading to uncertain diagnostic challenges, and association with kidney diseases.